Hatchery Performance of Nilem (Osteochilus hasselti) at Technical Implementation Unit of Fish Health and Environmental Laboratory (UPT LKIL), Pasuruan, East Java - Muhammad Browijoyo Santanumurti; Azza Fazania Zahira; Syahrul Isrofi; Mochamad Sahroni Hamzah; Muhammad Yahya; Ramzi H. Amran (Grouper, 2026)
Nilem fish (Osteochilus hasselti) is a freshwater fish commodity with enormous potential for the aquaculture sector. In aquaculture activities, fish hatchery is one of the crucial aspects. To date, the performance of nilem fish hatchery activities at the UPT LKIL has not been reported. This study was conducted to understand techniques for hatching Nilem fish using a semi-artificial system at the UPT LKIL Pasuruan, East Java. This study was conducted over 60 days at the UPT LKIL Pasuruan, East Java (Figure 1). The method used during this study was descriptive. The results showed that the hatchery activity at UPT LKIL Pasuruan, East Java showed 94% fertilized eggs, a 91% hatch rate, and an 88% survival rate. It can be concluded that the hatchery of Nilem fish at UPT LKIL Pasuruan showed good performance. These great results were supported by the use of ovaprim, good dissolved oxygen content, and fine protein feed. Although the temperature and pH were higher, UPT LKIL conducted water changes to neutralize them. UPT LKIL should prepare an indoor pond to prevent sunlight penetration so that the temperature and pH are not high.